Continuous Method: A Flexible Solution for Metal Length Expansion Measurement in the Modern Manufacturing Industry - Stephanus Goenawan (Metris: Jurnal Sains dan Teknologi, 2025)
Measurement of metal length expansion is crucial in the modern manufacturing industry as it impacts product design, production, and performance. Current conventional method (Discrete Methods/DM) relies on an initial reference length (L0), which limits the flexibility of in-situ and continuous measurements. This study compares the accuracy and flexibility of DM with the Continuous Method (CM), an approach that potentially eliminates the need for L0 after the initial measurement. Using numerical simulations on five metals, this study analyzes calculations for estimating metal length expansion under various heating scenarios. The results show that both methods provide similar differences in metal length thermal expansion values (difference <0.0001 m), confirming their comparative accuracy. However, CM proves significantly more flexible as it allows the calculation of metal length thermal expansion estimates at arbitrary temperatures without the need to refer to L0, unlike DM, which requires L0 for consistency. This flexibility makes CM more practical for both incremental and real-time measurements, supporting the integration of automation into precision manufacturing processes. Implications for the manufacturing industry include increased efficiency of in-situ measurements, reduced reliance on initial data, and the potential for better integration with continuous quality control systems and Digital Twins.